ANALISIS KUALITAS PELAYANAN PADA LABORATURIUM KLINIK GORA DI MONJOK MATARAM TAHUN 2016 - Khaerul Hadi (Valid: Jurnal Ilmiah, 2017)
This research analysis titled the quality of services in a Clinic Laboratory Gora. The purpose of this research was to know if the quality of service in terms of dimensions consisting of tangible services, reliability, responsiveness, assurance, empathy by Clinic Gora. Type this research, descriptive research in methods of data collection the sampel survey.The sample of the trophy is some 82 respondents to technique purposive sampling. Data collection techniques used are interviews, documentation and question form. Instrument data collection used is the questionnaire. Instrument the analysis used is analysis quality value services and diagrams of the kartesius. Based on the results of data analysis quality value services shows that the quality of services applied when viewed of the dimensions of service exhibited by clinic gora is in the category of less than good. This is shown by the result of reckoning NKJ 0.92 as much as .Where based on the assessment criteria that NKJ < 1, So the quality of services applied is less well. While on a Cartesian Diagram, the quality of service that is considered important by pasen for improved again in this Clinic Gora is on dimensions of service skills and knowledge of employees, cleanliness and comfort of the room, intensifitas information provided companies, companies will need pasien, guarantee an effective service, and courtesy to pasien.